Learning Strategies at SD Muhammadiyah 8 Tulangan During the Covid-19 Pandemic - Nadiyah Puspita Sari; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
Muhammadiyah 8 Tulangan Elementary School started with the establishment of a public school in 1949 which was built by several Muslims. So that a difference of opinion arose among the public school teachers who started not understanding the learning process. Islam, especially the application of fiqiyah to its students. During a pandemic like this, it has a very big impact on all sides of life, including in the world of education. The world of education seems to be a home as an educational institution that can make formal education. This was done due to government instructions and also because of the Covid-19 situation. Learning was finally carried out at home, including with Islamic religious education. At SD Muhammadiyah 8 Tulangan, which implemented a bold learning system during the covid-19 pandemic. During this bold learning in elementary school using zoom. In this case, the religious teachers of SD Muhammadiyah have innovation or escape from high boredom and stress.